INTERSECTIONS OF LANGUAGE EDUCATION, VISUAL LITERACIES, SEXUALITIES AND GENDERS: A(N) (IM)POSSIBLE ENCOUNTER? - Ferraz, Daniel; Mizan, Souzana (Trabalhos em lingüística aplicada, 2025)
ABSTRACT This article seeks to revisit the place of genders and sexualities in language education. It emphasizes the importance of addressing the languages of marginalized non-hegemonic bodies, including non-heterosexual/heteronormative bodies, bodies who continue to face abjection and exclusion in contemporary societies. It investigates the (im)possible and (im)probable encounter amongst language education and pedagogies focused on difference, sexualities, genders and their intersections with visual literacies. The research adopts a qualitative methodology and the methods of investigation involve review of literature, alongside digital document analysis through visual literacy methodologies in which images on social media platforms are interpreted as meaning making processes. Section 1 discusses the concepts of genders and sexualities by focusing on nonheteronormative and non-heterosexual existences. Section 2 contends that language education, visual literacies and gender and sexuality studies could and should be in constant dialogue in language classes. Finally, the article offers four praxeologies for language teacher education amidst the intersections of sexualities, and genders. RESUMO Este artigo busca revisitar o lugar dos gêneros e sexualidades na educação linguística. Enfatiza a importância de se abordar as linguagens dos corpos marginalizados e não hegemônicos, quais sejam, os corpos não heterossexuais/heteronormativos, que continuam a enfrentar a abjecção e a exclusão nas sociedades contemporâneas. Investiga o (im)possível e (im)provável encontro entre a educação linguística e as pedagogias focadas na diferença, nas sexualidades, nos gêneros e suas intersecções com os letramentos visuais. A pesquisa adota uma metodologia qualitativa e os métodos de investigação envolvem revisão de literatura, juntamente com análise de documentos digitais via letramentos visuais em que as imagens das mídias sociais são interpretadas como processos de construção de sentidos. A primeira Seção discute os conceitos de gêneros e sexualidades, concentrando-se em existências não heteronormativas e não heterossexuais. A segunda Seção defende que a educação linguística, os letramentos visuais e os estudos de gêneros e sexualidades podem e devem estar em constante diálogo nas aulas de línguas. Finalmente, o artigo oferece quatro praxiologias para a formação de professores de línguas em meio às intersecções de sexualidades e gêneros.